Rapid quantitative detection of Klebsiella pneumoniae in infants with severe infection disease by point-of-care immunochromatographic technique based on nanofluorescent microspheres - Chen, Ying; Sha, Lulu; Li, Wenqing; Zhou, Liuyan; Pei, Bing; Bian, Xinyu; Ji, Yongxin; Liu, Yiping; Wang, Li; Yang, Huan (Frontiers in Bioengineering and Biotechnology, 2023)
Background:Klebsiella pneumoniae (KP, K. pneumoniae) is one of the most important nosocomial pathogens that cause severe respiratory infections. As evolutionary high-toxic strains with drug resistance genes increase year by year, the infections caused by it are often accompanied by high mortality, which may be fatal to infants and can cause invasive infections in healthy adults. At present, the traditional clinical methods for detecting K. pneumoniae are cumbersome and time-consuming, and the accuracy and sensitivity are not high. In this study, nanofluorescent microsphere (nFM)-based immunochromatographic test strip (ICTS) quantitative testing platform were developed for point-of-care testing (POCT) method of K. pneumoniae. Methods: 19 clinical samples of infants were collected, the genus-specific gene of mdh was screened from K. pneumoniae. Polymerase chain reaction (PCR) combined with nFM-ICTS based on magnetic purification assay (PCR-ICTS) and strand exchange amplification (SEA) combined with nFM-ICTS based on magnetic purification assay (SEA-ICTS) were developed for the quantitative detection of K. pneumoniae. The sensitivity and specificity of SEA-ICTS and PCR-ICTS were demonstrated by the existing used classical microbiological methods, the real-time fluorescent quantitative PCR (RTFQ-PCR) and PCR assay based on agarose gel electrophoresis (PCR-GE). Results: Under optimum working conditions, the detection limits of PCR-GE, RTFQ-PCR, PCR-ICTS and SEA-ICTS are 7.7 × 10−3, 2.5 × 10−6, 7.7 × 10−6, 2.82 × 10−7 ng/μL, respectively. The SEA-ICTS and PCR-ICTS assays can quickly identify K. pneumoniae, and could specifically distinguish K. pneumoniae samples from non-K. pneumoniae samples. Experiments have shown a diagnostic agreement of 100% between immunochromatographic test strip methods and the traditional clinical methods on the detection of clinical samples. During the purification process, the Silicon coated magnetic nanoparticles (Si-MNPs) were used to removed false positive results effectively from the products, which showed of great screening ability. The SEA-ICTS method was developed based on PCR-ICTS, which is a more rapid (20 min), low-costed method compared with PCR-ICTS assay for the detection of K. pneumoniae in infants. Only need a cheap thermostatic water bath and takes a short detection time, this new method can potentially serve as an efficient point-of-care testing method for on-site detection of pathogens and disease outbreaks without fluorescent polymerase chain reaction instruments and professional technicians operation.